Experience in the treatment of enthesopathies by the method of local injection therapy - Anastasiya V. Sertakova (Лечащий Врач)
Background. The peculiarity of enthesopathies, or periarthropathies, is that, being an area of constant biomechanical stress and influencing adjacent hard and soft tissues, the enthesis forms an inflammatory impulse, leading to the development of inflammation in the synovial membrane adjacent to the enthesis. One of the pathogenetically substantiated steps in the treatment of enthesopathies is the method of periarticular administration of a chondroprotector. This method allows you to influence various parts of the inflammatory process and influence cellular respiration.Objective. To study the effect of local injection therapy with a metabolic specific stimulator of connective tissue repair on the course of periarthropathies.Materials and methods. 10 patients (6 women and 4 men aged 54.3 ± 0.4 years) were treated for enthesopathies by injection using a metabolically specific stimulator of connective tissue repair. Eight patients were diagnosed with "unilateral trochanteritis" and instrumentally confirmed, and two patients were diagnosed with "bilateral epicondylitis." Injections were performed periarticularly, 2 ml every 3 days, for a total of 5 injections. To evaluate the results, we used the VAS pain intensity scale, and also compared the range of motion in the hip and elbow joint before and after treatment. There were three control points in total before the start of treatment, at the end of treatment and 14 days after the last administration of the drug.Conclusion. It has been shown that when the drug is administered locally, the reparative stage and the outcome of inflammation in the tendon part of the muscles begin to predominate. Clinically, this is observed in the form of improved function and elimination of pain.